2007
DOI: 10.1186/1471-2229-7-21
|View full text |Cite
|
Sign up to set email alerts
|

Auxin and nitric oxide control indeterminate nodule formation

Abstract: BackgroundRhizobia symbionts elicit root nodule formation in leguminous plants. Nodule development requires local accumulation of auxin. Both plants and rhizobia synthesise auxin. We have addressed the effects of bacterial auxin (IAA) on nodulation by using Sinorhizobium meliloti and Rhizobium leguminosarum bacteria genetically engineered for increased auxin synthesis.ResultsIAA-overproducing S. meliloti increased nodulation in Medicago species, whilst the increased auxin synthesis of R. leguminosarum had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 36 publications
7
94
0
1
Order By: Relevance
“…LjHb1 would reduce the NO levels, thus limiting the defense responses and allowing the root colonization by rhizobia (Nagata et al 2009). On the other hand, the application of an NO scavenger to M. truncatula roots was shown to reduce the number of nodules (Pii et al 2007;del Giudice et al 2011) and to induce the downregulation of plant genes involved in nodule development (del Giudice et al 2011). Remarkably, NO has also been detected in differentiated nodules (Baudouin et al 2006;Pii et al 2007;Horchani et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LjHb1 would reduce the NO levels, thus limiting the defense responses and allowing the root colonization by rhizobia (Nagata et al 2009). On the other hand, the application of an NO scavenger to M. truncatula roots was shown to reduce the number of nodules (Pii et al 2007;del Giudice et al 2011) and to induce the downregulation of plant genes involved in nodule development (del Giudice et al 2011). Remarkably, NO has also been detected in differentiated nodules (Baudouin et al 2006;Pii et al 2007;Horchani et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…NO production is also induced by basal elicitors of plant responses such as bacterial lipopolysaccharides (LPS) (Zeidler et al 2004). Finally, evidence of NO involvement in plant symbioses is emerging; the use of NO-specific fluorescent probes has shown the occurrence of NO accumulation in the early (Shimoda et al 2005;Nagata et al 2008;del Giudice et al 2011) and late stages of the nitrogen-fixing symbiosis (NFS) that legumes establish with rhizobia (Baudouin et al 2006;Pii et al 2007;Horchani et al 2011). In addition, the application of a specific NO scavenger to M. truncatula roots inoculated with rhizobia resulted in a significantly reduced number of nodules (Pii et al 2007;del Giudice et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been a recent study demonstrating that a rhizobium strain modified to over produce IAA resulted in increased nodule number on Medicago sp. (Pii et al 2007). While we have reported here that WSM3457 produces IAA in vitro, at this stage it is not known whether this strain produces this compound in the rhizosphere of M. truncatula.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobia have the ability to synthesize auxin, and studies with Bradyrhizobium mutants deficient in IAA synthesis have shown that nodule numbers are reduced in soybean by a lack of rhizobial auxin (IAA) synthesis (Fukuhara et al, 1994). Moreover, increased nodule numbers were observed in M. truncatula plants inoculated with a Sinorhizobium meliloti strain that overproduces IAA (Pii et al, 2007). However, auxin produced by rhizobia is thought not to be necessary for the initiation events of the nodule, as in many legumes Nod factors alone can induce the early stages of nodule development, such as cortical cell divisions and auxin transport inhibition events leading to the initiation of indeterminate nodules (Mathesius et al, 1998a;Boot et al, 1999).…”
Section: Nodule Organogenesis Is Characterized By Changes In Auxin Rementioning
confidence: 99%